Prostate cancer immunotherapy-based strategies: an updated review emphasizing immune checkpoint inhibitors - Lu, Hua; Teng, Zhaojun; Wang, Jiajia; Zhang, Wenchao (Frontiers in Immunology, 2025)
Prostate cancer (PC) is one of the most common cancers that is diagnosed in about 10-15% of men in old age. It seems that the current treatments are not effective, and this leads to prostate cancer becoming the second-deadliest cancer. Treatments such as chemotherapy, radiotherapy, androgen deprivation therapy (ADT), and surgery are among these treatments. However, the possibility of disease recurrence after these treatments is high. Therefore, other methods have become necessary, and PC treatment is changing. One of the methods that has received much attention today is immunotherapy. Immunotherapy includes all interventions that help to treat cancer or any other disease by affecting the immune system’s responses. For this purpose, cytokines, cell therapy, and antibody-based methods can be used. Antibody-based treatments include immune checkpoint inhibitors (ICIs), and due to the high expression of immune checkpoint (ICP) molecules on the surface of prostate cancer cells and cancer stromal cells, these treatments have yielded promising results. Also, combining them with chemotherapy, surgery, and radiotherapy can help increase their efficiency. This review first updates standard treatments’ therapeutic efficacy and risk factors. Then, we will talk about different types of immunotherapies, emphasizing ICIs.